Pendidikan Lingkungan di Daerah Wisata Pantai Banding: Kampanye “Bawa Pulang Sampahmu” sebagai Dukungan terhadap SDGs 13 Climate Action - Simbolon, Khairunnisa; Darmastuti, Ari; Inayah, Astiwi; Fitria, Arie (Program Studi Hubungan Internasional FISIP UNILA, 2024)
Environmental education is an integral part of addressing sustainability challenges in tourist destinations, particularly in coastal areas that are vulnerable to the impacts of climate change. This Community Service activity implements the